2000
DOI: 10.1021/jm990589g
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Model of Lanosterol 14α-Demethylase of Candida albicans and Its Interaction with Azole Antifungals

Abstract: The three-dimensional structure of lanosterol 14alpha-demethylase (P450(14DM), CYP51) of Candida albicans was modeled on the basis of crystallographic coordinates of four prokaryotic P450s: P450BM3, P450cam, P450terp, and P450eryF. The P450(14DM) sequence was aligned to those of known proteins using a knowledge-based alignment method. The main chain coordinates of the core regions were transferred directly from the corresponding coordinates of P450BM3. The side chain conformations of the core regions were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
2
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 61 publications
12
161
2
5
Order By: Relevance
“…Modular structure design within protein families by using conserved structure elements in the active site (11), for example, forms the basis for 3D models, which drive SAR studies within protein families. This strategy even succeeds in protein families whose members have low sequence homology such as the cytochrome P450 superfamily, which consists of Ͼ2,000 members distributed across different organisms (12)(13)(14)(15).…”
Section: Translation Of Chemical Property Information Into Biologicalmentioning
confidence: 99%
“…Modular structure design within protein families by using conserved structure elements in the active site (11), for example, forms the basis for 3D models, which drive SAR studies within protein families. This strategy even succeeds in protein families whose members have low sequence homology such as the cytochrome P450 superfamily, which consists of Ͼ2,000 members distributed across different organisms (12)(13)(14)(15).…”
Section: Translation Of Chemical Property Information Into Biologicalmentioning
confidence: 99%
“…5 Indeed, several three-dimensional quantitative structure-activity relationship studies (3D QSAR) have been reported for different datasets of azole derivatives 2,6,[9][10][11][12] however, this strategy afforded models with moderate robustness and local predictive ability only. For instance, Di Santo and co-workers 1 report that their CoMFA model was contradicted by the synthesis and evaluation of novel compounds.…”
Section: Ketoconazole Nystatin Caspofugin Naftifinementioning
confidence: 99%
“…An initial step to overcome this dilemma was the resolution of the crystallographic structure of Mycobacterium tuberculosis sterol 14α-demethylase (MTCYP51) in complex with two azole inhibitors (4-phenylimidazole and fluconazole). 9 Yet, the bacterial source of this enzyme still poses as a problem for the development of 3D QSAR (ex. : comparative molecular field analysis -CoMFA) and 3D pharmacophore models, as these methods are highly dependent on molecular alignment.…”
Section: Ketoconazole Nystatin Caspofugin Naftifinementioning
confidence: 99%
“…cytochrome P450 14a-lanosterol demethylase, also termed CYP51. They are competitive inhibitors that bind reversibly to the haem iron moiety of CYP51 via a specific nitrogen atom in the azole ring (Hitchcock et al, 1990;Ji et al, 2000). The cytochromes P450 (P450s) are haem-thiolate enzymes that are able to oxygenate a large variety of substrates (Lewis, 1996).…”
Section: Cad-es-ms/ms Analysis Cad-es-ms/msmentioning
confidence: 99%